2021
DOI: 10.1093/jamia/ocab039
|View full text |Cite
|
Sign up to set email alerts
|

Clinical data sharing improves quality measurement and patient safety

Abstract: Objective Accurate and robust quality measurement is critical to the future of value-based care. Having incomplete information when calculating quality measures can cause inaccuracies in reported patient outcomes. This research examines how quality calculations vary when using data from an individual electronic health record (EHR) and longitudinal data from a health information exchange (HIE) operating as a multisource registry for quality measurement. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Besides the above facts, data quality is considered very valuable for the health systems, in particular for patient data that contains information about diagnosis, medications, hospital treatments, and so on. Thus, referring to D’Amore et al (2021), “Overall, the integrated data showed that 79% of patients in the study had records located within more than one facility.”…”
Section: Research Backgroundmentioning
confidence: 99%
“…Besides the above facts, data quality is considered very valuable for the health systems, in particular for patient data that contains information about diagnosis, medications, hospital treatments, and so on. Thus, referring to D’Amore et al (2021), “Overall, the integrated data showed that 79% of patients in the study had records located within more than one facility.”…”
Section: Research Backgroundmentioning
confidence: 99%
“…Ultimately, the effectiveness of HIE will depend on community understanding of the role of HIE and overcoming barriers to support sharing of health data for enabling effective healthcare delivery [3,4,39,44]. HIE has been shown to improve care, through the availability of health information at critical times of need [45,46]. HIE enables critical information to be disseminated, supporting smooth transitions of care from acute events, such as stroke [47].…”
Section: Information Disseminationmentioning
confidence: 99%
“…To develop and implement this framework in practice, an important challenge to overcome is data sharing. Although data sharing has been shown to improve quality measurement and patient safety (D'Amore et al 2021), it is often infeasible to share patientlevel data across hospitals due to confidentiality concerns. Traditional methods for hospital quality measurement have relied on either fixed or random effects models (Austin et al 2003, Jones & Spiegelhalter 2011, Normand et al 1997).…”
Section: Causal Inference For Quality Measurementmentioning
confidence: 99%